Astigmatism management in cataract surgery with Precizon(®) toric intraocular lens: a prospective study - Vale, C. (2017)
PURPOSE: The purpose of this study was to evaluate the visual and refractive outcomes and rotational stability of the new aspheric Precizon(®) toric intraocular lens (IOL) for the correction of corneal astigmatism in cataract surgery. SETTING: Department of Ophthalmology, Hospital Geral de Santo António - Centro Hospitalar do Porto, EPE and Hospital de Pedro Hispano, Matosinhos, Portugal. DESIGN: This was a prospective clinical study. PATIENTS AND METHODS: A total of 40 eyes of 27 patients with corneal astigmatism greater than 1.0 diopter (D) underwent cataract surgery with implantation of Precizon(®) toric IOL. IOL power calculation was performed using optical coherence biometry (IOLMaster(®)). Outcomes of uncorrected (UDVA) and best-spectacle corrected distance visual acuities (BCDVA), refraction, and IOL rotation were analyzed at the 1st week, 1st, 3rd, and 6th month's evaluations. RESULTS: The median postoperative UDVA was better than preoperative best-spectacle corrected distance visual acuity (0.02 [0.06] logMAR vs 0.19 [0.20] logMAR, P<0.001). At 6 months, postoperative UDVA was 0.1 logMAR or better in 95% of the eyes. At last follow-up, the mean spherical equivalent was reduced from -3.35±3.10 D to -0.02±0.30 D (P<0.001) with 97.5% of the eyes within ±0.50 D of emmetropia. The mean preoperative keratometric cylinder was 2.34±0.95 D and the mean postoperative refractive cylinder was 0.24±0.27 D (P<0.001). The mean IOL rotation was 2.43°±1.55°. None of the IOLs required realignment. CONCLUSION: Precizon(®) toric IOL revealed very good rotational stability and performance regarding predictability, efficacy, and safety in the correction of preexisting regular corneal astigmatism associated with cataract surgery.